Burnout among paramedic students at a university in Johannesburg South Africa - C Stein; T Sibanda (African Journal of Health Professions Education, 2016)
Background. Burnout has been studied in several emergency medical services contexts and has been found to be high compared with that found in other health professions. Although burnout among students has been described in several healthcare disciplines, this has not been done in the field of prehospital emergency care.Objectives. To determine the prevalence of burnout among students in a 4-year university paramedic degree programme and to assess whether there was any significant difference in the prevalence of burnout among students during the 4 years of study.Methods. In this cross-sectional survey all students enrolled in a 4-year university paramedic degree programme were invited to participate. The questionnaire consisted of 19 questions from the Copenhagen Burnout Inventory (CBI), combined with distractor questions. Responses were analysed descriptively and one-way analysis of variance was used to compare CBI scores across the 4 academic years of study.Results. An 85% (n=93) response rate was obtained. The overall prevalence of burnout was 31%. Mean CBI scores across all academic years of study were highest for personal burnout, followed by work-related burnout and patient care-related burnout. The highest prevalence of students with burnout was in the 4th year, as was the highest prevalence of work-related and personal burnout. The second highest prevalence of students with burnout was in the 1st year, as was the highest prevalence of patient care-related burnout. No significant difference was found in CBI total burnout scores across the 4 years of study.Conclusion. Although there are no directly comparable data, the prevalence of burnout in this group of students appears to be high, particularly in the 1st and 4th years of study. Steps should be taken to ensure access to social and psychological support to avoid a negative impact on academic success and student wellbeing.